2020
DOI: 10.15625/1811-4989/18/1/15271
|View full text |Cite
|
Sign up to set email alerts
|

Potential anti-tumor activites of extract from fresh leaves of the male papaya (Carica papaya L.) collected in Ha Tinh province

Abstract: Nowadays, the percentage of people with cancer is increasing. There are many methods used to treat cancer such as surgery, chemotherapy, the radiation, etc. In addition, the use of medicinal plants, natural products, is also popularly applied for cancer patients. Using 90% ethanol as the extraction solvent, we produced 4 kinds of concentrated extracts from dried flowers, dried leaves, fresh flowers, fresh leaves of male papaya (Carica papaya Linn). In vitro study, the extracts of dried flowers, fresh flowers d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…After years of research, many vegetables have been reported to be toxic to cancer cells. One such vegetable is papaya 4 . The discovery further helps scientists believe that other vegetables can also bear this superior property.…”
Section: Introductionmentioning
confidence: 99%
“…After years of research, many vegetables have been reported to be toxic to cancer cells. One such vegetable is papaya 4 . The discovery further helps scientists believe that other vegetables can also bear this superior property.…”
Section: Introductionmentioning
confidence: 99%